Embodied cognition of aging - Vallet, Guillaume T. (Frontiers in Psychology, 2015)
Embodiment is revolutionizing the way we consider cognition by incorporating the influence of our body and of the current context within cognitive processing. A growing number of studies which support this view of cognition in young adults stands in stark contrast with the lack of evidence in favor of this view in the field of normal aging and neurocognitive disorders. Nonetheless, the validation of embodiment assumptions on the whole spectrum of cognition is a mandatory step in order for embodied cognition theories to become theories of human cognition. More pragmatically, aging populations represent a perfect target to test embodied cognition theories due to concomitant changes in sensory, motor and cognitive functioning that occur in aging (these theories predict direct interactions between them). Finally, the new perspectives on cognition provided by these theories might also open new research avenues and new clinical applications in the field of aging. The present article aims at showing the value and interest to explore embodiment in normal and abnormal aging as well as introducing some potential theoretical and clinical applications.